Evolution of the Electrical Displacement and Energy Dissipation of Lead Zirconate-Titanate Ceramics under Cyclical Load - Sheng Cang; Jiankang Chen; Chunsheng Lu (Advances in Materials Science and Engineering)
In this paper, the electromechanical behavior of lead zirconate-titanate ceramics (P51) has been characterized and modeled. The variation of the energy dissipation and peak electrical displacement of the P51 ceramic has been investigated in details. The total strain of P51 under cyclical loading consists of elastic deformation (εije), immediate ferroelectric domain switching deformation (εijd), and time-dependent deformation (εijc). Thus, an expression for the energy dissipation of P51 can be theoretically derived. In addition, a practical method for calculating the dissipated energy has been proposed by integrating the curve of a hysteresis loop. The experimental results show that the peak electrical displacement and dissipated energy both decrease monotonously with the increase of the number of cycles. Furthermore, ferroelectric 90° domain switching was observed by X-ray diffraction (XRD) and the percentage of domain switching has been calculated by the variation of the peak intensity ratio of (002) to (200) at about 45 degrees. Then, grain debonding, crack, and crush were found around voids inside the specimen by using scanning electron microscope (SEM). It is indicated that switching of more capable-switch domains stimulates larger dissipated energy and a bigger peak electrical displacement at the initial cyclic loading. Finally, an exponential functional model has been proposed to simulate the peak evolution of electrical displacement based on the energy dissipation of P51 ceramics under cyclical load.